TRADE MECHANISMS OF 2008 – 2009 GLOBAL FINANCIAL AND ECONOMIC CRISIS EFFECTS PRODUCED ON TRANSFORMATION ECONOMIES - Adamyk, Viktoriya; Savka, Andriy (Journal of European Economy, 2017)
The pre-feasibility study is carried out of the effects the 2008-2009 global financial and economic crisis produced on the economic and social development of Ukraine, Russia, Poland, and Czech Republic. In particular, the effects of financial and economic volatility produced through trade channels are studied. The challenging areas of economic structures are detected in the analyzed countries. Specific attention is focused on the study of Ukrainian foreign trade imbalance, on the reasons of its origin, and consequences for the social and economic development of the country. The recommendations are developed on the mechanisms for equilibrating the Ukrainian foreign trade balance.